Prevalent Dominant Acinetobacter baumannii ST191/195/208 Strains in Bloodstream Infections Have High Drug Resistance and Mortality - Niu T; Guo L; Kong X; He F; Ru C; Xiao Y (Infection and Drug Resistance, 2023)
Tianshui Niu,1,2,* Lihua Guo,2,* Xiaoyang Kong,2,* Fei He,1 Chuhui Ru,1 Yonghong Xiao2 1Department of Respiratory and Critical Care Medicine, Affiliated Hangzhou Chest Hospital, Zhejiang University School of Medicine, Hangzhou, 310058, People’s Republic of China; 2State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, The First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, 310003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yonghong Xiao, State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, The First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, 310003, People’s Republic of China, Tel/Fax +86 571 87236421, Email xiaoyonghong@zju.edu.cnBackground: Different sequence types of Acinetobacter baumannii (AB) have their own epidemiological characteristics, drug resistance, and toxicity.Methods: AB bloodstream infection (BSI) in the First Affiliated Hospital of Medical College of Zhejiang University from January 2012 to December 2017 were classified by multilocus sequence typing. Clinical data of patients were retrospectively analyzed, drug resistance and toxicity were respectively studied by drug sensitivity and complement killing tests.Results: 247 unduplicated AB strains were collected, and ST191/195/208, the main epidemic dominant strain, accounted for 70.9%. Patients with ST191/195/208 on infection had higher white blood cell (10.8 vs 8.9, p = 0.004), neutrophil% (89.5 vs 86.9, p = 0.005), neutrophil count (9.5 vs 7.1, p = 0.021), D-dimer (6.7 vs 3.8, p = 0.000), total bilirubin (27.0 vs 21.5, p = 0.038), pronatriuretic peptide (324 vs 164, p = 0.042), C-reactive protein (82.5 vs 56.3, p = 0.048), clinical pulmonary infection score (CPIS; 7.33 ± 2.30 vs 6.50 ± 2.72, p = 0.045), and acute physiology and chronic health evaluation-II (APACHE-II; 19.620 ± 5.1850 vs 17.648 ± 6.1251, p = 0.011). Patients with ST191/195/208 had more complications, including pulmonary infection (p = 0.041), septic shock (p = 0.009), and multiple organ failure (p = 0.019). Patients with ST191/195/208 had higher 3 day mortality (24.6% vs 13.9%, p = 0.043), 14 day mortality (46.8% vs 26.8%, p = 0.003), and 28 day mortality (55.0% vs 32.4%, p = 0.001). ST191/195/208 strains had higher drug resistance to most antibiotics, and higher survival rate at 90% normal serum concentration (p < 0.001).Conclusion: ST191/195/208 strains predominate in the hospital and prevails in patients with severe infections with increased multidrug antimicrobial resistance and excessive mortality compared to any other AB stains.Keywords: Acinetobacter baumannii, bloodstream infection, MLST, mortality, toxicity